2002
DOI: 10.1007/s00422-002-0333-2
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory fusion and the stochastic structure of postural sway

Abstract: We analyze the stochastic structure of postural sway and demonstrate that this structure imposes important constraints on models of postural control. Linear stochastic models of various orders were fit to the center-of-mass trajectories of subjects during quiet stance in four sensory conditions: (i) light touch and vision, (ii) light touch, (iii) vision, and (iv) neither touch nor vision. For each subject and condition, the model of appropriate order was determined, and this model was characterized by the eige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
142
1
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(170 citation statements)
references
References 38 publications
22
142
1
3
Order By: Relevance
“…The duration of 20 to 25 seconds was selected to ensure the stationarity of CoP signals. Recent studies have shown that the CoP may be non-stationary when recorded for longer durations, typically exceeding 30 seconds [16,17,18,19]. Data were collected in two consecutive trials where the subjects were asked either to open or close their eyes throughout the stance period.…”
Section: Protocol and Data Analysismentioning
confidence: 99%
“…The duration of 20 to 25 seconds was selected to ensure the stationarity of CoP signals. Recent studies have shown that the CoP may be non-stationary when recorded for longer durations, typically exceeding 30 seconds [16,17,18,19]. Data were collected in two consecutive trials where the subjects were asked either to open or close their eyes throughout the stance period.…”
Section: Protocol and Data Analysismentioning
confidence: 99%
“…The 'smoothness' of the COP trajectories hints at strong deterministic components in the stochastic postural sway dynamics and comparatively weak influences of noise (see also Collins andDe Luca 1993, 1995;Riley et al 1999;Riley and Turvey 2002). Using linear systems theory and corresponding identification techniques, Kiemel et al (2002) similarly concluded that COP trajectories reflect a mixture of deterministic and stochastic components. However, this more traditional approach tends to downplay the importance of the repeatedly demonstrated non-linear character of the COP dynamics.…”
Section: Introductionmentioning
confidence: 98%
“…Their model accounted for the characteristic mean-squared displacement and correlation functions typically seen in postural sway; however, it lacked an explicit control mechanism, which is our primary interest here. Kiemel et al (2002) used high-order linear and optimal control theory models to estimate postural states. Higher order models require many parameters and thus are very complex.…”
Section: Introductionmentioning
confidence: 99%